Effects of Thermal Treatment on Mineral Composition and Pore Structure of Coal - Bin Liu; Teng Teng; Zhenhua Jiao; Shaobo Li (Geofluids)
With the increasing depth of coalbed methane (CBM) exploitation, temperature becomes the main factor affecting the efficiency of CBM exploitation. The change of temperature has significant influence on the mineral composition and pore structure of coal. To study the effects of thermal treatment on mineral composition and pore structure of coal, X-ray diffraction (XRD) test, scanning electron microscopy (SEM) test, and mercury intrusion test were carried out for three groups of coal. The mineral composition and pore structure of coal specimens after thermal treatment (25, 50, 75, and 100°C) were analyzed. The results show that the main mineral compositions of three groups of coal specimens after different temperatures are basically unchanged, and the maximum diffracted intensity after different temperature treatments decreases first and then increases with the increasing temperature. The count of fissures decreases first and then increases with temperature, and the count of pores increases first and then decreases with the increasing temperature. The velocity of mercury injection in high pressure (100~400 MPa) of coal specimens increases first and then decreases with temperature. The porosity, pore area, median pore diameter, and average pore diameter increase with the increasing temperatures. The volume of microfracture decreases, then increases, and finally decreases. The volume of macropore and mesopore increases slowly, and that of transition pore decreases slowly with the increasing temperature. Meanwhile, the volume of micropore increases first and then decreases during the process of thermal treatment. The fractal dimension of pore size ranges from 2.6 to 2.9 and increases linearly with the increasing temperature.